2014
DOI: 10.1051/0004-6361/201423440
|View full text |Cite
|
Sign up to set email alerts
|

Rosette globulettes and shells in the infrared

Abstract: Context. Giant galactic H ii regions surrounding central young clusters show compressed molecular shells, which have broken up into clumps, filaments, and elephant trunks interacting with UV light from central OB stars. Tiny, dense clumps of subsolar mass, called globulettes, form in this environment. Aims. We observe and explore the nature and origin of the infrared emission and extinction in these cool, dusty shell features and globulettes in one H ii region, the Rosette nebula, and search for associated new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Gahm et al (2007) derived masses from extinction measures indicating that most objects have masses < 13 M J (Jupiter masses). Follow-up near-infrared (NIR) imaging and radio molecular line observations of the larger globulettes in the Rosette nebula, hereafter labelled RN, showed that these objects are dense and that the gas is molecular even close to the surface layers (Gahm et al 2013;hereafter called G13;Mäkelä et al 2014). Mass estimates derived from modelling the molecular line emission (based on the gas content) were found to be similar, but systematically higher compared to those derived from extinction (based on the dust content).…”
Section: Introductionmentioning
confidence: 99%
“…Gahm et al (2007) derived masses from extinction measures indicating that most objects have masses < 13 M J (Jupiter masses). Follow-up near-infrared (NIR) imaging and radio molecular line observations of the larger globulettes in the Rosette nebula, hereafter labelled RN, showed that these objects are dense and that the gas is molecular even close to the surface layers (Gahm et al 2013;hereafter called G13;Mäkelä et al 2014). Mass estimates derived from modelling the molecular line emission (based on the gas content) were found to be similar, but systematically higher compared to those derived from extinction (based on the dust content).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these background clouds may be globules accelerated by the expansion of the Rosette Nebula H II region. With near-infrared imaging and mid-infrared and far-infrared data from Spitzer IRAC and Herschel PACS, Mäkelä et al (2014Mäkelä et al ( , 2017 investigated the physical properties and star formation activity of the globulettes and globules that lie in front of the Rosette Nebula and are associated with the C1 cloud. They found that the masses of globulettes are subsolar and the masses of globules are 9.5-11.6 M and that the globules RN A and RN E have velocities around 3 km s −1 which is similar to the velocity of cloud C1.…”
Section: Rmc Background Molecular Cloudsmentioning
confidence: 99%
“…The average velocity of the Rosette Nebula is 16.7 km s −1 (Dent et al 2009), therefore, it can be assumed that globules RN A and RN E have been accelerated by the Rosette Nebula H II region about 13.7 km s −1 toward the earth. Taking the results of Mäkelä et al (2014Mäkelä et al ( , 2017 as a reference on the masses of globules and the acceleration by the Rosette Nebula H II region, we consider the background molecular clouds that have masses less than 15 M and velocities less than 30.4 km s −1 as the possible globules blown out of the H II region on the far side. We recalculated the masses of the background molecular clouds with a fixed distance of 1.4 kpc rather than the kinematic distances derived from the Galactic rotation curve and it is found that 17 background molecular clouds satisfy the mass and velocity criterion.…”
Section: Rmc Background Molecular Cloudsmentioning
confidence: 99%
“…Reipurth et al 2003;De Marco et al 2006;Gahm et al 2007) and even in the NIR (e.g. Mäkelä et al 2014), as they are seen as silhouettes against the bright nebular background emission. Despite their small sizes (4 to 20 ), the globulettes in the Rosette and Carina nebulae were well detected in 12 CO and 13 CO (3-2) and (2-1) lines at Atacama pathfinder experiment (APEX) (Gahm et al 2013;Haikala et al 2017).…”
Section: Introductionmentioning
confidence: 99%